Lightweight sealing strip microcellular foam material and production method thereof

By using composite reinforcement agents and modified metal salts in microporous foaming materials, combined with pre-sulfurized foaming technology, the problems of complex process, high cost and poor dispersion in the prior art are solved, and the lightweight sealing strip micro-layers are achieved The performance and safety of pore foaming materials are improved.

CN119264570APending Publication Date: 2025-01-07JIANGSU RUNTAIYIN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411516692.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing microporous foaming materials have complex preparation processes, high equipment requirements, high cost and poor material dispersion, and the comprehensive performance needs to be improved.

Method used

Using ethylene propylene ternary rubber as the main raw material, lightweight sealing strip microporous foaming materials are prepared by adding composite reinforcement, foaming agent, plasticizer, etc., and ultrasonic dispersion and carboxylation are used to treat silica and accumulation. stone, modified composite metal salt, combined with pre-sulfurized foaming process, improves the dispersion and performance of the material.

Benefits of technology

The comprehensive performance improvement of foamed materials is achieved, including excellent tensile and fracture performance, moderate foaming density and high combustion safety, reducing the risk of equipment operation and preparation costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of foam material preparation, and particularly discloses a lightweight sealing strip microcellular foam material and a production method thereof. The lightweight sealing strip microcellular foam material is prepared from the following raw materials: 80-120 parts of ethylene propylene diene monomer, 40-65 parts of a composite reinforcing agent, 8-15 parts of a foaming agent, 6-12 parts of a plasticizer, 2-6 parts of composite metal salt, 1-5 parts of a vulcanizing agent, 1-5 parts of an accelerant and 1-5 parts of an active agent. According to the lightweight sealing strip microcellular foam material provided by the invention, the ethylene propylene diene monomer is used as a main raw material, and the comprehensive performance of the foam material is ensured by adding the reinforcing agent, the foaming agent, the plasticizer and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of foam material preparation, and in particular relates to a lightweight sealing strip microporous foam material and a production method thereof. Background Art

[0002] Lightweight sealing strip microporous foam material is a new type of sealing material, which is commonly used in the automotive, construction, electronics and other industries. Its main features include: (1) Lightweight: Compared with traditional sealing materials, microporous foam materials have a lower density, which can effectively reduce the overall weight and improve the energy efficiency and performance of the product; (2) Microporous structure: This material has a tiny pore structure inside, which enables it to have good elasticity and flexibility while maintaining strength, and can adapt to different sealing requirements; (3) Excellent sealing performance: Microporous foam materials can effectively block the penetration of moisture, dust and air, provide good sealing effect, and extend the service life of the product; (4) Weather resistance: This material usually has strong weather resistance, can resist the erosion of ultraviolet rays, temperature changes and chemicals, and is suitable for use in various environments.

[0003] Usually, microporous foaming materials are prepared with ethylene propylene diene monomer (EPDM) as raw material; as a weather-resistant, insulating and flexible rubber material, it has been widely used in the fields of sealing rubber rings. However, EPDM rubber is a non-self-reinforcing rubber and has the characteristics of low unsaturation. During its application, it is often necessary to add reinforcing materials, vulcanizers and other functional substances. There have been many related studies in the prior art. For example, patent document CN116063728A provides a preparation method of microporous foaming rubber material, which uses supercritical carbon dioxide as a microporous foaming agent and uses ionic liquid TPP-PF6. The supercritical operating pressure is high, the requirements for equipment and materials are high, and the amount of ionic liquid is small, and the preparation cost is high; patent document CN107163415A provides a dense glue microporous foaming rubber material for automobile sunroof sealing strips and preparation method, a lightweight sealing strip with high compressibility and elasticity was obtained, but its overall performance needs to be further improved; Journal literature (Deng Fuquan. Preparation and Performance Research of EVA / POE / EPDM / OMMT Nanocomposite Foaming Materials [D]. Shaanxi University of Science and Technology, 2013. DOI: 10.7666 / d.Y2307683.) uses montmorillonite to compound EPDM-containing polymers to obtain foaming materials. On the one hand, the types of polymers used are many and the cost is relatively uncontrollable. On the other hand, montmorillonite is directly added to the polymer, which is prone to uneven dispersion and poor compatibility.

[0004] Therefore, it is worthwhile to continuously study the preparation of microporous foam materials, simplify the process and improve the comprehensive performance. Therefore, the lightweight sealing strip microporous foam material of the present invention is proposed. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a lightweight sealing strip microporous foam material and a production method thereof. The prepared microporous foam material has excellent tensile and fracture properties, moderate foaming density, high combustion safety and good comprehensive performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solution: In a first aspect, a lightweight sealing strip microporous foam material is provided, which is prepared from the following raw materials, in parts by weight: 80 to 120 parts of EPDM rubber, 40 to 65 parts of a composite reinforcing agent, 8 to 15 parts of a foaming agent, 6 to 12 parts of a plasticizer, 2 to 6 parts of a composite metal salt, 1 to 5 parts of a vulcanizing agent, 1 to 5 parts of an accelerator, and 1 to 5 parts of an activator.

[0007] As a further preferred embodiment of the technical solution of the present invention, the preparation of the composite reinforcing agent comprises the following steps: (1) Adding silica to N,N-dimethylformamide, ultrasonically dispersing it uniformly, then adding succinic anhydride and KH550 in equal molar ratios, and dispersing it uniformly again; then stirring it; after the stirring is completed, filtering, washing, and drying it to obtain pretreated silica for later use; (2) mixing the rectorite with sodium hydroxide and subjecting it to high temperature treatment, and after the treatment is completed, the pretreated rectorite is obtained; (3) adding the pretreated rectorite into the tartaric acid solution and stirring the solution; after the treatment, centrifuging, washing and drying the solution to obtain the modified rectorite; (4) Adding the modified rectorite to an ethanol solution containing KH550, and then adding the pre-modified silica, and heating the solution; after the treatment, filtering, washing, drying, and finally grinding and sieving, a composite reinforcing agent is obtained.

[0008] As a further preferred embodiment of the technical solution of the present invention, in step (1), the mass ratio of silicon dioxide, N,N-dimethylformamide and succinic anhydride is 10:50-100:0.3-0.8; The stirring treatment temperature is room temperature, and the stirring treatment time is 4 to 8 hours.

[0009] As a further preferred embodiment of the technical solution of the present invention, in step (2), the mass ratio of rectorite to sodium hydroxide is 1:0.3-0.6, the high temperature treatment temperature is 790-810°C, and the treatment time is 0.5-4h.

[0010] As a further preferred embodiment of the technical solution of the present invention, in step (3), the concentration of the tartaric acid solution is 0.08-0.12 mmol / L; the dosage ratio of the pretreated rectorite to the tartaric acid solution is 1 g: 3-10 mL; the stirring treatment temperature is 25-30° C., and the treatment time is 4-8 h.

[0011] As a further preferred embodiment of the technical solution of the present invention, in step (4), the concentration of KH550 is 3-5wt%; the dosage ratio of modified rectorite, pre-modified silica, and ethanol solution is 1g: 1-2g: 5-10mL; The heating treatment temperature is 65~70℃ and the treatment time is 0.5~4h; The sieving mesh number is 250~300 mesh.

[0012] As a further preferred embodiment of the technical solution of the present invention, the composite metal salt is formed by mixing copper sulfate and aluminum sulfate in a molar ratio of 1:1.

[0013] As a further preferred embodiment of the technical solution of the present invention, the foaming agent is one or two of azodicarbonamide and di(benzenesulfonylhydrazide)ether; The plasticizer is one or more of paraffin oil, aromatic oil, and naphthenic oil; The vulcanizing agent is one or two of sulfur and diethylstyrene peroxide; The accelerator is one or more of accelerator M, accelerator TT, and accelerator D; The active agent is one or more of stearic acid, zinc oxide and zinc stearate.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned lightweight sealing strip microporous foam material, comprising the following steps: S1. Preparation of solution: adding the composite metal salt to water, stirring and dissolving evenly to obtain a metal aqueous solution for standby use; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 16 to 48 hours, evaporating the aqueous solution under stirring conditions, and then drying at 125 to 155° C. to obtain a modified composite material after drying; S3, plasticizing: on an open mill, plasticizing the EPDM rubber at 40°C for 3-10 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 6 to 15 minutes to obtain a mixed rubber; S5. Pre-vulcanization: Add the mixed rubber into the Haake rheometer, then add 0.04-0.1 parts of vulcanizing agent, and then pre-vulcanize at 170°C for 8-15 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 3 to 8 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a heat circulation oven for foaming. After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0015] As a further preferred embodiment of the technical solution of the present invention, in step S1, the total concentration of the metal aqueous solution is 0.6-1wt%; In step S6, the foaming temperature is 180-190° C., and the foaming time is 10-45 min.

[0016] Thirdly, considering the comprehensive performance values ​​of the foaming material of the present invention, it is very suitable to be used as a sealing material for automobile interior decoration.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The lightweight sealing strip microporous foam material provided by the present invention uses EPDM rubber as the main raw material, and the comprehensive performance of the foam material is ensured by adding a reinforcing agent, a foaming agent, a plasticizer, etc.

[0018] (2) The lightweight sealing strip microporous foam material provided by the present invention is prepared by using silicon dioxide and rectorite as the main raw materials. The raw materials are common and the two are treated accordingly before use. Specifically: first, the silicon dioxide is carboxylated, which is beneficial to improve the dispersibility of silicon dioxide and improve its compatibility with EPDM rubber. At the same time, the carboxylated silicon dioxide is beneficial to the grafting and compounding with the modified rectorite; the rectorite is first treated with sodium hydroxide at high temperature, which is beneficial to improve the pore structure of the rectorite and preliminarily improve the adsorption and loading performance; then the rectorite is treated with tartaric acid, which is beneficial to further improve the adsorption performance of the rectorite and further improve the subsequent loading efficiency of the composite metal ions. Finally, the treated silicon dioxide and rectorite are introduced with amino groups, etc., which improves the compatibility of the composite reinforcing material with EPDM rubber, and is beneficial to the carboxyl group contained in the modified silicon dioxide and the amino group provided by KH550 to form a hydrogen bond system, thereby ensuring the stabilizer of the composite reinforcing material system and its dispersibility in the rubber matrix. In summary, the lightweight sealing strip microporous foam material provided by the present invention uses rectorite with certain flame retardant properties, which can enhance the wear resistance of the rubber matrix; silicon dioxide can improve the wear resistance, tensile and tear strength of the rubber matrix. The use of the two can improve the comprehensive performance of the EPDM rubber foam material. Through preliminary modification, the above-mentioned effects can be maximized.

[0019] (3) The lightweight sealing strip microporous foam material provided by the present invention introduces the use of composite metal salts, and in the preparation process, composite reinforcing materials are first used to impregnate and load the composite metal salts. The purpose is twofold: on the one hand, since EPDM rubber is a non-self-reinforcing rubber, it is necessary to add a filler reinforcing agent to have better comprehensive performance. The use of metal salts is conducive to further improving the dispersibility of the composite reinforcing materials, which not only ensures that the reinforcing materials and the rubber matrix avoid stratification or phase separation during the foaming process, but also ensures the dispersibility and mechanical properties of the reinforcing materials in the rubber matrix; on the other hand, the loading of metal ions is conducive to improving the coordination and bonding of the rubber matrix and improving the stability of the foaming material. Specifically, in terms of the selection and use of metal salts, the present invention has found through screening that the composite effect of copper and aluminum is the best, the raw materials of the two are common, and the addition of aluminum is conducive to further improving the fire resistance and flame retardancy of the foaming material.

[0020] (4) The lightweight sealing strip microporous foam material provided by the present invention, the groups of the composite reinforcing material (such as carboxyl) and the introduced groups (such as amino groups of coupling agents), etc., are conducive to improving the chelating performance of metal salts and improving the impregnation and adsorption effect of the composite reinforcing material on metal salts, thereby balancing the cross-linking vulcanization and foaming speed of the rubber, thereby achieving the purpose of improving the performance of the foaming material and ensuring the performance of the rubber.

[0021] (5) The lightweight sealing strip microporous foam material provided by the present invention adopts a pre-vulcanization foaming process during the preparation process, thereby avoiding the high-pressure operation existing in the traditional ultra-high pressure foaming, reducing the requirements for equipment operation and the danger of operation, and being safer.

[0022] In conclusion, the present invention uses EPDM rubber as the main raw material and prepares a lightweight foaming material with good comprehensive performance by selecting appropriate functional additives such as reinforcing materials, which has good application prospects. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0024] In the present invention, the rectorite used in each embodiment was purchased from Hubei Mingliu Rectorite Technology Co., Ltd.

[0025] In the present invention, the EPDM rubber used in each embodiment has a brand number of 4640 and is produced by DowDuPont Company of the United States.

[0026] In the present invention, the mentioned accelerator M, whose chemical name is 2-thiolbenzothiophene; the accelerator TT, whose chemical name is tetramethylthiuram disulfide; and the accelerator D, whose chemical name is diphenylguanidine, are all purchased from the market. Azodicarbonamide is purchased from Shanghai Jieyu Industry and Trade Co., Ltd.

[0027] In the present invention, the silicon dioxide is purchased from Evonik Degussa A200.

[0028] It should be particularly emphasized that in the present invention, the size of the foamed material prepared can be flexibly selected according to actual needs during the preparation of the standard sample. The open mill, Haake rheometer, etc. involved are all common rubber production equipment and can be purchased through market channels.

[0029] Example 1

[0030] A lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g of EPDM rubber, 50g of a composite reinforcing agent, 10g of a foaming agent (azodicarbonamide), 9g of a plasticizer (paraffin oil), 4.5g of a composite metal salt (obtained by mixing copper sulfate and aluminum sulfate in an equal molar ratio), 3.5g of a vulcanizing agent (sulfur), 3g of an accelerator (obtained by mixing accelerator TT and accelerator D of equal mass), and 2.5g of an active agent (stearic acid).

[0031] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion. Then stir at room temperature for 5 hours. After the stirring treatment, filter, wash and dry to obtain pretreated silica for standby use. The mass ratio of silica, N,N-dimethylformamide and succinic anhydride is 10:75:0.5. (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.45 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:6 mL, and stirring the solution at 30°C for 5.5 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68°C for 1.5 h. After the treatment, the composite reinforcing agent was obtained by filtering, washing, drying, and finally grinding and sieving through 250 mesh. The dosage ratio of the modified rectorite, pre-modified silica, and ethanol solution was 1 g: 1.5 g: 8 mL.

[0032] In this embodiment, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: adding the mixed rubber to the Haake rheometer, then adding 0.065 parts of vulcanizing agent, and then pre-vulcanizing at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0033] Example 2

[0034] A lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g of EPDM rubber, 48g of a composite reinforcing agent, 9.5g of a foaming agent (azodicarbonamide), 9.5g of a plasticizer (paraffin oil), 4.2g of a composite metal salt (obtained by mixing copper sulfate and aluminum sulfate in an equal molar ratio), 3.7g of a vulcanizing agent (sulfur), 2.8g of an accelerator (obtained by mixing accelerator TT and accelerator D of equal mass), and 2.7g of an active agent (stearic acid).

[0035] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion, and then disperse evenly again; then stir at room temperature for 5 hours; after the stirring treatment is completed, filter, wash, and dry to obtain pretreated silica for standby use; the mass ratio of silica, N,N-dimethylformamide, and succinic anhydride is 10:80:0.45; (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.5 and subjecting the mixture to a high temperature treatment at 800°C for 1 hour. After the treatment, the pretreated rectorite is obtained; (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:5.5 mL, and stirring the solution at 30°C for 5 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68°C for 1.5 h. After the treatment, the composite reinforcing agent was obtained by filtering, washing, drying, and finally grinding and sieving through 250 mesh. The dosage ratio of the modified rectorite, pre-modified silica, and ethanol solution was 1 g: 1.5 g: 8 mL.

[0036] In this embodiment, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: add the mixed rubber into the Haake rheometer, then add 0.07 parts of vulcanizing agent, and then pre-vulcanize at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0037] Example 3

[0038] A lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g of EPDM rubber, 52g of a composite reinforcing agent, 10.5g of a foaming agent (azodicarbonamide), 8.5g of a plasticizer (paraffin oil), 4.8g of a composite metal salt (obtained by mixing copper sulfate and aluminum sulfate in an equal molar ratio), 3.2g of a vulcanizing agent (sulfur), 2.5g of an accelerator (obtained by mixing accelerator TT and accelerator D of equal mass), and 2.9g of an active agent (stearic acid).

[0039] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion, and then disperse evenly again; then stir at room temperature for 5 hours; after the stirring treatment is completed, filter, wash, and dry to obtain pretreated silica for standby use; the mass ratio of silica, N,N-dimethylformamide, and succinic anhydride is 10:80:0.55; (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.48 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:5 mL, and stirring the solution at 30°C for 6 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68 °C for 2 h. After the treatment, the composite reinforcing agent was obtained by filtering, washing, drying, and finally grinding and sieving through 250 mesh. The amount ratio of modified rectorite, pre-modified silica, and ethanol solution was 1 g: 1.5 g: 8 mL.

[0040] In this embodiment, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.75%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: add the mixed rubber into the Haake rheometer, then add 0.07 parts of vulcanizing agent, and then pre-vulcanize at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0041] Comparative Example 1 Compared with Example 1, the silicon dioxide in this comparative example is not pretreated. Specifically, a lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g EPDM rubber, 50g composite reinforcing agent, 10g foaming agent (azodicarbonamide), 9g plasticizer (paraffin oil), 4.5g composite metal salt (obtained by mixing copper sulfate and aluminum sulfate in an equal molar ratio), 3.5g vulcanizing agent (sulfur), 3g accelerator (obtained by mixing accelerator TT and accelerator D of equal mass), and 2.5g active agent (stearic acid).

[0042] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Take silica raw material and set aside; (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.45 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:6 mL, and stirring the solution at 30°C for 5.5 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), followed by the addition of silica, and the mixture was heated at 68°C for 1.5 h. After the treatment, the mixture was filtered, washed, dried, and finally ground and sieved through 250 mesh to obtain a composite reinforcing agent. The dosage ratio of the modified rectorite, silica, and ethanol solution was 1 g:1.5 g:8 mL.

[0043] In this comparative example, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: adding the mixed rubber to the Haake rheometer, then adding 0.065 parts of vulcanizing agent, and then pre-vulcanizing at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0044] Comparative Example 2 Compared with Example 1, the comparative example does not perform tartaric acid treatment on the rectorite. Specifically, a lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g EPDM rubber, 50g composite reinforcing agent, 10g foaming agent (azodicarbonamide), 9g plasticizer (paraffin oil), 4.5g composite metal salt (obtained by mixing copper sulfate and aluminum sulfate in an equal molar ratio), 3.5g vulcanizing agent (sulfur), 3g accelerator (obtained by mixing accelerator TT and accelerator D of equal mass), and 2.5g active agent (stearic acid).

[0045] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion. Then stir at room temperature for 5 hours. After the stirring treatment, filter, wash and dry to obtain pretreated silica for standby use. The mass ratio of silica, N,N-dimethylformamide and succinic anhydride is 10:75:0.5. (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.45 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) Pre-modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68°C for 1.5 h. After the treatment, the mixture was filtered, washed, dried, and finally ground and sieved through 250 mesh to obtain a composite reinforcing agent. The dosage ratio of pre-modified rectorite, pre-modified silica, and ethanol solution was 1 g:1.5 g:8 mL.

[0046] In this comparative example, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: adding the mixed rubber to the Haake rheometer, then adding 0.065 parts of vulcanizing agent, and then pre-vulcanizing at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0047] Comparative Example 3 Compared with Example 1, this comparative example uses only copper sulfate as the metal salt, and no aluminum sulfate is used. Specifically, a lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g EPDM rubber, 50g composite reinforcing agent, 10g foaming agent (azodicarbonamide), 9g plasticizer (paraffin oil), 4.5g metal salt (copper sulfate), 3.5g vulcanizing agent (sulfur), 3g accelerator (obtained by mixing equal masses of accelerator TT and accelerator D), and 2.5g active agent (stearic acid).

[0048] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion. Then stir at room temperature for 5 hours. After the stirring treatment, filter, wash and dry to obtain pretreated silica for standby use. The mass ratio of silica, N,N-dimethylformamide and succinic anhydride is 10:75:0.5. (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.45 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:6 mL, and stirring the solution at 30°C for 5.5 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68°C for 1.5 h. After the treatment, the composite reinforcing agent was obtained by filtering, washing, drying, and finally grinding and sieving through 250 mesh. The dosage ratio of the modified rectorite, pre-modified silica, and ethanol solution was 1 g: 1.5 g: 8 mL.

[0049] In this comparative example, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: adding the mixed rubber to the Haake rheometer, then adding 0.065 parts of vulcanizing agent, and then pre-vulcanizing at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0050] Comparative Example 4 Compared with Example 1, the metal salt in this comparative example only uses aluminum sulfate instead of copper sulfate. Specifically, a lightweight sealing strip microporous foam material is prepared from the following raw materials by weight: 100g EPDM rubber, 50g composite reinforcing agent, 10g foaming agent (azodicarbonamide), 9g plasticizer (paraffin oil), 4.5g metal salt (aluminum sulfate), 3.5g vulcanizing agent (sulfur), 3g accelerator (mixed with equal mass of accelerator TT and accelerator D), and 2.5g active agent (stearic acid).

[0051] Wherein, the preparation of the composite reinforcing agent comprises the following steps: (1) Add silica to N,N-dimethylformamide, and then add succinic anhydride and KH550 in equal molar ratios to disperse evenly after ultrasonic dispersion. Then stir at room temperature for 5 hours. After the stirring treatment, filter, wash and dry to obtain pretreated silica for standby use. The mass ratio of silica, N,N-dimethylformamide and succinic anhydride is 10:75:0.5. (2) mixing rectorite and sodium hydroxide in a mass ratio of 1:0.45 and subjecting the mixture to a high temperature treatment at 795°C for 1 hour. After the treatment, the pretreated rectorite is obtained. (3) adding the pretreated rectorite to a 0.1 mmol / L tartaric acid solution at a dosage ratio of 1 g:6 mL, and stirring the solution at 30°C for 5.5 h; after the treatment, centrifuging, washing, and drying the solution to obtain the modified rectorite; (4) The modified rectorite was added to an ethanol solution containing KH550 (the concentration of KH550 was 4 wt%), and then pre-modified silica was added, and heated at 68°C for 1.5 h. After the treatment, the composite reinforcing agent was obtained by filtering, washing, drying, and finally grinding and sieving through 250 mesh. The dosage ratio of the modified rectorite, pre-modified silica, and ethanol solution was 1 g: 1.5 g: 8 mL.

[0052] In this comparative example, a method for preparing the above-mentioned lightweight sealing strip microporous foam material is also provided, comprising the following steps: S1. Preparation of solution: Add the composite metal salt into water, stir and dissolve evenly to obtain a metal aqueous solution (the total mass fraction of metal ions is 0.8%), and set aside; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 24 hours, evaporating the aqueous solution under stirring conditions, and then drying at 130° C. to obtain a modified composite material; S3, plasticizing: on an open mixing mill, plasticizing the EPDM rubber at 40° C. for 5 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 8 minutes to obtain a mixed rubber; S5, pre-vulcanization: adding the mixed rubber to the Haake rheometer, then adding 0.065 parts of vulcanizing agent, and then pre-vulcanizing at 170°C for 10 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 4 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a thermal cycle oven for foaming (185°C, 25 minutes). After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

[0053] The foamed materials prepared in the examples and comparative examples were tested for performance as follows: 1. Foaming density: refer to GB / T6343-2009; 2. Hardness: refer to GB / T 531.1-2008; 3. Tensile strength: refer to GB / T 528-2009; 4. Elongation at break: refer to GB / T 528-2009; 5. Smoke density: refer to GB / T 8627-2007.

[0054] The specific test results are shown in Table 1.

[0055] Table 1 Test results of embodiments and comparative examples Group <![CDATA[Foaming density g / cm 3 > Hardness (Shore A) Tensile strength / MPa Elongation at break / % Smoke density Example 1 0.090 48 5.7 346 68 Comparative Example 1 0.088 44 4.8 252 80 Comparative Example 2 0.087 42 5.2 298 83 Comparative Example 3 0.086 45 5.4 306 92 Comparative Example 4 0.088 46 5.3 313 77 It can be seen from Table 1 that the density of the foamed material prepared by the present invention is 90kg / m 3 , has a certain comfort and cushioning effect; at the same time, the hardness is moderate, not too soft or too hard, and can provide a certain support; the tensile strength and elongation at break are also moderate; the foaming material also has very good combustion performance and high safety. In general, the foaming material prepared by the present invention is very suitable for the fields of automobile interior decoration.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lightweight sealing strip microporous foam material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 80-120 parts of EPDM rubber, 40-65 parts of composite reinforcing agent, 8-15 parts of foaming agent, 6-12 parts of plasticizer, 2-6 parts of composite metal salt, 1-5 parts of vulcanizing agent, 1-5 parts of accelerator and 1-5 parts of activating agent.

2. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: The preparation of the composite reinforcing agent comprises the following steps: (1) Adding silica to N,N-dimethylformamide, ultrasonically dispersing it uniformly, then adding succinic anhydride and KH550 in equal molar ratios, and dispersing it uniformly again; then stirring it; after the stirring is completed, filtering, washing, and drying it to obtain pretreated silica for later use; (2) mixing the rectorite with sodium hydroxide and subjecting it to high temperature treatment, and after the treatment is completed, the pretreated rectorite is obtained; (3) adding the pretreated rectorite into the tartaric acid solution and stirring the solution; after the treatment, centrifuging, washing and drying the solution to obtain the modified rectorite; (4) Adding the modified rectorite to an ethanol solution containing KH550, and then adding the pre-modified silica, and heating the solution; after the treatment, filtering, washing, drying, and finally grinding and sieving, a composite reinforcing agent is obtained.

3. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: In step (1), the mass ratio of silicon dioxide, N,N-dimethylformamide and succinic anhydride is 10:50-100:0.3-0.8; The stirring treatment temperature is room temperature, and the stirring treatment time is 4 to 8 hours.

4. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: In step (2), the mass ratio of rectorite to sodium hydroxide is 1:0.3-0.6, the high temperature treatment temperature is 790-810°C, and the treatment time is 0.5-4h.

5. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: In step (3), the concentration of the tartaric acid solution is 0.08-0.12 mmol / L; the dosage ratio of the pretreated rectorite to the tartaric acid solution is 1 g: 3-10 mL; the stirring treatment temperature is 25-30° C., and the treatment time is 4-8 h.

6. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: In step (4), the concentration of KH550 is 3-5wt%; the dosage ratio of modified rectorite, pre-modified silica, and ethanol solution is 1g: 1-2g: 5-10mL; The heating treatment temperature is 65~70℃ and the treatment time is 0.5~4h; The sieving mesh number is 250~300 mesh.

7. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: The composite metal salt is prepared by mixing copper sulfate and aluminum sulfate in a molar ratio of 1:

1.

8. The lightweight sealing strip microporous foam material according to claim 1, characterized in that: The foaming agent is one or two of azodicarbonamide and di(benzenesulfonylhydrazide)ether; The plasticizer is one or more of paraffin oil, aromatic oil, and naphthenic oil; The vulcanizing agent is one or two of sulfur and diethylstyrene peroxide; The accelerator is one or more of accelerator M, accelerator TT, and accelerator D; The active agent is one or more of stearic acid, zinc oxide and zinc stearate.

9. A method for preparing the lightweight sealing strip microporous foam material according to any one of claims 1 to 8, characterized in that: The steps include: S1. Preparation of solution: adding the composite metal salt to water, stirring and dissolving evenly to obtain a metal aqueous solution for standby use; S2, preparation of modified composite material: adding a composite reinforcing agent to the metal aqueous solution obtained in step S1, immersing for 16 to 48 hours, evaporating the aqueous solution under stirring conditions, and then drying at 125 to 155° C. to obtain a modified composite material after drying; S3, plasticizing: on an open mill, plasticizing the EPDM rubber at 40°C for 3-10 minutes to obtain plasticized rubber; S4, mixing: adding the modified compound obtained in step S2, as well as the plasticizer, accelerator, and activator to the plasticized rubber, and mixing at 50° C. for 6 to 15 minutes to obtain a mixed rubber; S5. Pre-vulcanization: Add the mixed rubber into the Haake rheometer, then add 0.04-0.1 parts of vulcanizing agent, and then pre-vulcanize at 170°C for 8-15 minutes to obtain pre-vulcanized rubber; S6. Secondary mixing and foaming: transfer the pre-vulcanized rubber to an open mixer, add the foaming agent and the remaining vulcanizing agent, and mix for 3 to 8 minutes; then cut the sheets and prepare the standard samples; finally, place the standard samples in a heat circulation oven for foaming. After the treatment is completed, the lightweight sealing strip microporous foam material is obtained.

10. The preparation method according to claim 9, characterized in that: In step S1, the total concentration of the metal aqueous solution is 0.6-1wt%; In step S6, the foaming temperature is 180-190° C., and the foaming time is 10-45 min.

Citation Information

Patent Citations

  • Automobile skylight sealing strip non-porous rubber microcellular foamed rubber and preparation method thereof

    CN107163415A

  • Preparation method of microcellular foaming rubber material and sealing strip

    CN116063728A